2018
DOI: 10.3389/fnagi.2018.00206
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Modulates the Cerebello-Thalamo-Cortical Circuit and Cognitive Brain Regions in Patients of Parkinson's Disease With Tremor

Abstract: Objective: To investigate the effect of acupuncture on Parkinson's disease (PD) patients with tremor and its potential neuromechanism by functional magnetic resonance imaging (fMRI).Methods: Forty-one PD patients with tremor were randomly assigned to true acupuncture group (TAG, n = 14), sham acupuncture group (SAG, n = 14) and waiting group (WG, n = 13). All patients received levodopa for 12 weeks. Patients in TAG were acupunctured on DU20, GB20, and the Chorea-Tremor Controlled Zone, and patients in SAG acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 43 publications
(41 reference statements)
1
37
0
1
Order By: Relevance
“…Other measures of brain activity, degree centrality (DC), and amplitude low-frequency fluctuation (ALFF) values, also showed decreases after acupuncture compared to sham. Meanwhile, increased ReHo values were observed within the thalamus and motor cortex [17]. The results of this clinical study demonstrate that functional imaging can directly detect and measure acupuncture-induced brain activities even at the level of the neural network.…”
Section: Functional Mri Studies In Humansmentioning
confidence: 62%
See 2 more Smart Citations
“…Other measures of brain activity, degree centrality (DC), and amplitude low-frequency fluctuation (ALFF) values, also showed decreases after acupuncture compared to sham. Meanwhile, increased ReHo values were observed within the thalamus and motor cortex [17]. The results of this clinical study demonstrate that functional imaging can directly detect and measure acupuncture-induced brain activities even at the level of the neural network.…”
Section: Functional Mri Studies In Humansmentioning
confidence: 62%
“…In human studies, acupuncture stimulations that directly modulate brain activity can also be observed [17,18]. An example of this was carried out by Li and colleagues [17] who used fMRI to investigate the potential neuromechanism of acupuncture on tremor in patients with Parkinson's disease. Li and colleagues compared fMRI signals in patients with Parkinson's disease who were either in the true acupuncture group (TAG) or the sham acupuncture group (SAG).…”
Section: Functional Mri Studies In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of needling at GB20 affects the regulation of retinal gene expression, is still unclear and may be extraordinarily complex, since the site of GB20 is at the back of the neck, far from the eyes ( Figure 1A ). A previous functional magnetic resonance imaging study revealed that needling at GB20 was able to regulate neural activity within the visual region of the brain (Li et al, 2018 ). It is reported that needling treatment also regulated the expression of nerve growth factor and brain-derived neurotrophic factor in retina (Pagani et al, 2006 ), which may regulate retinal gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most important source of data that proves the beneficial effects of acupuncture in treatment of signs and symptoms in Parkinson's disease is provided from functional neuroimaging studies. These studies have shown huge modifications in neural functions after acupuncture sessions [68,69].…”
Section: Multimodal Exercise Programmentioning
confidence: 99%